GAMBARAN PENGETAHUAN TERHADAP KEPATUHAN PEMAKAIAN ALAT PELINDUNG DIRI PADA PEKERJA DI PT. BINA SARANA SUKSES (BSS) - Agus, Agus; Lisa Anita Sari; Noprival, Noprival (Bajang Institute, 2024)
Until now, the use of personal protective equipment has been a significant problem in the field of Occupational Health and Safety. Workers who do not use personal protective equipment will be at risk of occupational accidents. Workers do not use personal protective equipment due to a lack of understanding of the benefits and importance of personal protective equipment in protecting themselves from the risk of injury or exposure to hazardous materials in the work environment. This study aims to see how the description of workers' knowledge of compliance with the use of personal protective equipment. This research method is using a quantitative method with an analytic descriptive design. The statistical test used is the univariate test. The results showed that most of the 88 respondents, 63 (71.6%) respondents who had good knowledge about personal protective equipment and 52 (59.1%) respondents who were not compliant in the use of personal protective equipment. It is hoped that the results of this study can be preliminary data and add references to research in the work environment, especially research related to occupational health and safety.